PENERAPAN PRINSIP-PRINSIP HAK ASASI MANUSIA DALAM PENCEGAHAN TINDAK PIDANA KEKERASAN SEKSUAL PADA ANAK - Mupakkirah, Zakiyah (TADULAKO MASTER LAW JOURNAL, 2024)
The purpose of this paper is to analyze: 1) Application of the Principles of Human Rights in Crimes of Sexual Violence against Children. 2) How to Prevent Criminal Acts of Sexual Violence against Children. The writing method used is normative legal research or library legal research using a statute approach, case approach, and conceptual approach. The results showed that: 1) the application of the Principles of Human Rights in Criminal Acts of Sexual Violence on Children. there are four principles of human rights, namely universality, indivisibility, interdependent, and intrrelated, which are derivative principles from the principle of universality. Sexual violence committed against children can hinder their progress and prevent them from enjoying human rights and freedoms and also hinder the achievement of the principle of equality. 2) Efforts to prevent criminal acts of sexual violence against children preventive efforts or preventive efforts and repressive efforts. Preventive efforts, namely by conducting socialization related to education, guidance, and awareness to the general public about various forms of crime including sexual violence against children within the family. While repressive efforts are a form of effort made in order to show how the eradication of crimes that occur by being realized through criminal law.